Korupcija Latvijas Valsts policijā - Bebers, Kārlis (Latvijas Universitāte, 2010)
Bakalaura darba tēma „Korupcija Latvijas Valsts policijā” attiecināma uz Latvijā aktuālo korupcijas tēmu. Bakalaura darba mērķis ir pētīt korupcijas īpatnības un riskus Latvijas Valsts policijā. Nolūkā sasniegt mērķi autors izvirzīja sekojošus uzdevumus – definēt korupcijas jēdzienu, analizēt policijas darbinieku atbildību par koruptīvajiem nodarījumiem, noskaidrot korupcijas riskus Valsts policijā. Būtisks pētījuma uzdevums ir saistīts ar koruptīvo noziedzīgo nodarījuma līmeni, struktūru un dinamiku Valsts policijā, kā arī disciplinārpārkāpumu analīzi. Viens no darba uzdevumiem ir saistīts ar korupciju veicinošo faktoru Valsts policijā pētīšanu un novēršanas iespēju apzināšanu. Lai izpildītu darba uzdevumus, tika izmantotas dažādas kriminoloģijas pētīšanas metodes: statistiskā, ekspertu vērtējuma, aptauja, speciālistu intervijas metode. Darbā ir izmantoti par korupcijas tēmu senāk veiktie socioloģiskie pētījumi, kurus ir veikušas dažādas nevalstiskas organizācijas, piem., Providus, Sabiedrība par atklātību –Delna, Tirgus un sabiedriskās domas pētījumu centrs SKDS.

Subject of the bachelor’s paper is “Corruption in the State police of Latvia” therefore author put forward goals to research corruptions characteristic and those risks in the State police of Latvia. In bachelor’s paper author advanced following tasks: define the risks of corruption, analyze the liability of police officers about corrupt offences and clarify the risks of corruption in the State police of Latvia. The author concludes that that the problem of corruption in Latvia is burning question because whereat indicated even several international organizations and European Union institutions. These current economic difficulties and cut of funding and other factors make difficulties to prevent corruption in the State police of Latvia. Latvia is post – Soviet state and the country relatively brief period of existent has not been sufficient to give rise legal, democratic traditions. In society is a common perception that corruption exist in the police, especially in the Track police. Analyzing this problem the author examined researches of corruption, statistical data, interviewed and surveyed police officers of State police of Latvia. The author these and others factors analyzed in bachelor’s paper and offered several solutions how to prevent corruption such as make more research on corruption in the State police of Latvia, to ensure that the various ant - corruption program which offer author not only with statistic character data but also with criminological research character. As well as author hold a view that need more educate employee of the State police of Latvia about the risks of corruption and about corrupt efences.
Corruption in the State police of Latvia
Keywords: Juridiskā zinātne